The reward strategy and performance measurement (evidence from Malaysian insurance companies) - Ong, Tze San; Yip, Mei Theen; Teh, Boon Heng (Centre for Promoting Ideas, 2012)
Purpose: The purpose of this paper is to contribute to the body of knowledge in the area of reward systems, particularly the total reward framework. The reward framework determined serve as the principal guideline for the small and medium enterprise in Malaysia. Design/methodology/approach: The paper used an intensive case study of two selected insurance companies, known as Agency A and Company B. The two companies are different in terms of their size and capital. Findings: The findings suggest that the use of financial and objective measures are the main concern in designing the reward systems of the organization, companies are gradually incorporated non-financial measures in their reward systems. Other remarkable findings include identical rewards are tied to different working nature which is found to be deviate from the normal norms. Research limitation/implications: The reward framework identified can be used as guideline for the small and medium enterprises in Malaysia to further understand the function of reward system, thus design and implement their unique and attractive reward system. Originality/value: The paper shows that rewards lead to increase in both financial and non-financial performance which will also enhance companies’ reputation, as well as increase the recruitment possibility where more manpower will make a stronger team. Effective rewards mechanism will shift from fulfilling employees’ basic requirement to self-actualization as they are growing with the business.